ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN (Studi Kasus Dadi Cellular) - Ageng Saepudin Kanda; Kamal Maulana (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to analyze the influence of quality of service on consumer satisfaction at DADI CELLULAR counters. High quality of service is considered an important factor in creating sustained consumer satisfaction and maintaining consumer loyalty in the highly competitive telecommunications industry. This study was quantified by survey methods. The study sample consisted of 10 consumers who were users of DADI CELLULAR quota counter services, randomly selected from location sharing. Data were collected through questionnaires designed to measure consumers' perceptions of quality of service which included their level of satisfaction. Data analysis was performed using statistical techniques. The results of this study are expected to provide a better understanding of the relationship between Dadi cellular counter service quality and customer satisfaction. In addition, the study is also expected to provide input for Dadi cellular management in improving the quality of their services, Meeting consumer expectations, and maintaining a competitive market share.